Post-Traumatic Growth in Families with HIV/AIDS - Firdiani, Norberta Fauko; Iqballa, Lisda; Harsono, Yudi Tri (Jurnal Psikologi Islam, 2021)
HIV is one of chronic diseases which can cause the emergence of traumatic event towards its sufferers. The traumatic event which can be faced strongly will lead individuals to positive change which is called as growth after trauma. The purpose of this research is to know the growth description after trauma on individuals with PLWHA status. This research used descriptive-qualitative method and data collection was done through semi-structured interview technique. The results obtained from the research is that there is positive change on both subjects which indicates the existence of post traumatic growth with PLWHA status. That change covers the improvement in term of individual’s power, the correlation with other people, the rewards towards life, the identification of new possibility, and spiritual change.